Improved atom equivalents method for converting density functional theory energies calculated on molecular mechanics structures to heats of formation - Duchowicz, Pablo Román (2001)
We present an improved atom equivalents method for converting Density Functional Theory energies calculated on molecular mechanics structures to enthalpies of formation. The introduction of bond parameters to an original sent of atom parameters yields a sensible improvement of the enthalpy predictions. The comparison with other similar approaches shows that our present method is a rather better calculation scheme. Some further possible improvements are pointed out.